2013
DOI: 10.1021/es403251g
|View full text |Cite
|
Sign up to set email alerts
|

A Model to Estimate the Population Contributing to the Wastewater Using Samples Collected on Census Day

Abstract: An important uncertainty when estimating per capita consumption of, for example, illicit drugs by means of wastewater analysis (sometimes referred to as "sewage epidemiology") relates to the size and variability of the de facto population in the catchment of interest. In the absence of a day-specific direct population count any indirect surrogate model to estimate population size lacks a standard to assess associated uncertainties. Therefore, the objective of this study was to collect wastewater samples at a u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
112
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 138 publications
(115 citation statements)
references
References 16 publications
2
112
0
1
Order By: Relevance
“…The de facto population connected to an STP may not coincide with the determined de jure population 11,13 . It is because the former is population equivalent and accounts for tourist and the difference between daytime and nighttime populations, while the later is based on the latest census.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The de facto population connected to an STP may not coincide with the determined de jure population 11,13 . It is because the former is population equivalent and accounts for tourist and the difference between daytime and nighttime populations, while the later is based on the latest census.…”
Section: Introductionmentioning
confidence: 98%
“…More recently, O'Brien et al 13 found the artificial sweetener acesulfame and the anti-epileptic gabapentin effective in estimating the population (the "de facto population") connected to sewage treatment plants (STPs) in Australia on a census day (the "de jure population"). The results revealed that such stable substances can be used as indicators of populations in river basins, as well as of the proportion of treated or untreated wastewater (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous efforts have focused on improving the accuracy (trueness and 130 precision) of different analytical methods, and inter-laboratory studies were conducted in order to evaluate and harmonize the different analytical procedures being used (Castiglioni et al, 2013;Thomas et al, 2012). Uncertainties associated with the population estimates have recently been conceptually reduced (Lai et al, 2015;O'Brien et al, 2014), as well as the uncertainty related to wastewater sampling (Ort et al, 2010). Furthermore, sample collection, storage and preparation 135 methods have been evaluated, deducing critical, substance-specific parameters: i) solvent and temperature used during the evaporation of solid-phase extraction (SPE) extracts, and ii) biomarker stability in the wastewater matrix and silanisation of glassware (Baker and Kasprzyk-Hordern 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, a ubiquitous biomarker could be found that has no other source than human excretion and is stable during transport in sewers (Chen et al 2014). So far, pharmaceutical residues have been successfully combined with Bayesian inference (O'Brien et al 2014). Although transformation of certain drugs during transport in sewers may affect SBE, this is just starting to be investigated (Thai et al 2014).…”
Section: Back-calculation and Uncertaintymentioning
confidence: 99%